PERAN MAHASISWA DALAM MENGHADAPI ETIKA AKUNTANSI STUDI KUALITATIF DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Amalia Devi Wulandari; Hwihanus, Hwihanus (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This qualitative research seeks to examine how accounting students at the University of 17 August 1945 Surabaya address ethical challenges in accounting. This study investigates students' views on the accountant's code of ethics and how they implement ethical principles in real-life situations throughout their learning and practice experiences. The findings of the study indicate that accounting students recognize the significance of ethics in accounting practices, especially in maintaining the integrity, reliability and transparency of financial information. They also recognize that accounting ethics involves honesty, integrity, objectivity, and professionalism in decision making and financial reporting. This research found that ethics education in the accounting curriculum still needs to be improved to form more effective ethical behavior. Therefore, This study offers suggestions for improving the accounting education curriculum at the University of 17 August 1945 Surabaya to better address the demands of the workforce and the ethical challenges faced in the field.